The Effect of Know What Learn (KWL) Strategy to Improve Students’ Reading Comprehension in Descriptive Text at Tenth Grade SMAN Negeri 8 Tebo - Auladiyah, Robiatul; Nurni Khairita , Martiya; Widia Nanda , Dodi (The Future of Education Journal, 2022)
Reading comprehension is a reading activity to absorb information from the reading material and understand or know the implied meaning and meaning of the reading so that it can be conveyed properly to the reader. The research aims to find out the effect of KWL strategy to improve students’ reading comprehension. This research used quantitative. Reading test was used as the instrument to taken the data. This research used two classes which is experimental class and control class. There were 14 students who registered in control class and 14 students in experiment class. The result showed the students’ mean score in the post-test of the experimental class and control class, the mean score in the post-test of the experimental class was 68.29 and the mean score in the post-test of the control class was 47.93. T-test was used to answer the research question and conducted in both the experimental class and control class by used IBM SPSS 20. The result of T-test showed that the significance paired samples T-test is 0.000<0.05, which mean H0 is rejected and Ha is accepted. Thus, it is concluded that there is a significant effect of using KWL strategy to improve students’ reading comprehension.